(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
The objective of this work is to analyze the impact of the Covid-19 pandemic on industry in the municipality of Ponta Grossa after the 1st quarter of restrictive measures and social isolation. The study seeks to answer what is the short-term effect on revenue, production and employment of the regional industry, given the scenario of uncertainty and the endogenous and exogenous factors that influenced demand in the period. The suggested hypothesis was that, industries whose type of good produced was considered essential, tend to be less sensitive to impacts than those whose product was considered non-essential. The results showed that 97% of the companies that had the biggest reduction in revenue and 83% in production, in fact, were those specialized in essential products. For employment, the classification of the asset had no significant effect, however the behavior of the revenue explained 77% of the dismissals.